Transylvania Television. Night of the thingy - Heagle, Michael J.; Gallagher, Matthew; Leomark Studios (Firm) ([United States] : Transylvania Television Workshop, 2012)
"Le Shoc's new direction for the station goes horribly wrong"--
Originally released as a television program in 2012
Series created by Michael Heagle, Gordon Smuder.
Editor, Sam Heyn ; music, International Espionage, Coffin Daggers, DJ Sothoth, DJRuss.
This movie is suitable for 14-year-olds and older.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 25, 2018)
Keywords: Monsters -- Drama; Transylvania (Romania) -- Drama; Animated television programs; Television comedies; Webisodes; Internet videos; Streaming video